Humanisme Pendidikan Islam dalam Serial Anime Naruto - Azami, Tomi (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2023)
The phenomenon of dehumanization still often occurs in the world of education, in the form of bullying, exclusion and superiority over others. This is an inhumane action and has deviated from Islamic teachings, so it needs to be corrected. The process of humanism in Islamic education can be done in various ways, one of which is through the Naruto anime series. This research aims to analyze the humanist value of Islamic education or the human values contained in the Naruto Anime series. This research is a type of qualitative literature study. So research data is obtained from journals, books and other documents related to research. Meanwhile, the data analysis technique in this research uses pragmatic content analysis. The results of the research show that there are humanist values of Islamic education in the Naruto series which are dominated by hablum mina annas values. In the Naruto series, a process of becoming (becoming) and self-perfection as an individual (self-improvement) is shown. There are six main things that are the focus of humanism in Islamic Education namely, (1) common sense, (2) individualism towards independence, (3) thirst for knowledge, (4) pluralism education, (5) contextualism which is more concerned with functions than symbols, and (6) a balance between reward and punishment.